Manajemen Kepala Madrasah dalam Memaksimalkan Seleksi Penerimaan Peserta Didik Baru (PPDB) di MTs Maulana Malik Ibrahim (MMI) Gresik - Abdul Aziz (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
This research focuses on the planning, organizing, and implementation of the selection process at MTs. MMI Gresik, with the objective of analyzing the planning, organizing, and implementation of the student admission selection at MTs. MMI Gresik to meet expectations. The research approach is descriptive qualitative. Data collection techniques include interviews and documentation. The data analysis techniques used by the researcher include data reduction, presentation, and conclusion drawing. The validity of the data was tested using triangulation. The results of the research show that in the planning stage of student admissions, the head of the madrasa at MTs. MMI Gresik prepared committee decision letters, meeting plans, implementation schedules, budgets, admission requirements, scholarship criteria, and promotion plans. In the organizing stage, the process followed the student admission SOP with coordination through meetings and WhatsApp groups. The implementation of student admissions ran smoothly with promotions through banners, brochures, websites, Instagram, TikTok, and Facebook. A total of 95% or 96 new students underwent the TPA and BTQ tests and re-registered. However, 5% only completed the registration form without taking the tests or re-registering because they chose another school. During Matsama on July 17, 2023, 10 new students were accepted at MTs. MMI. For the next student admissions, it is important to involve stakeholders such as the madrasa committee, student guardians, madrasa supervisors, and psychologists in determining selection needs.